Compared Some Estimators Ordinary Ridge Regression And Bayesian Ridge Regression With Practical Application - عبودي عماد حازم; حمود احمد جبار (Journal of Economics and Administrative Sciences, 2019)
Maulticollinearity is a problem that always occurs when two or more predictor variables are correlated with each other. consist of the breach of one basic assumptions of the ordinary least squares method with biased estimates results, There are several methods which are proposed to handle this problem including the method To address a problem and method To address a problem , In this research a comparisons are employed between the biased method and unbiased method with Bayesian using Gamma distribution method addition to Ordinary Least Square method, We will use the simulation to compare these methods using the mean squares error criteria. The method of biased gave good results by using sizes different samples.